ANALISIS KETEPATAN PENGGUNAAN EJAAN, TANDA BACA, DAN PILIHAN KATA DALAM MENULIS KARANGAN DESKRIPSI DENGAN MEDIA FLASH CARD PADA SISWA : ANALYSIS OF THE ACCURACY OF SPELLING, PUNCHMARK, AND WORD CHOICE IN WRITING DESCRIPTIVE ESSAY USING FLASH CARD MEDIA BY STUDENTS - Aisyah Apriani (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2024)
This study aims to analyze in depth the accuracy of the use of formal language aspects—particularly spelling, punctuation, and word choice (diction)—in fourth-grade students' descriptive essays after the application of flashcards as visual stimuli. The study used a descriptive qualitative approach with a case study design, conducted at MI Yaspi VII Sumbersari. The research subjects consisted of 22 fourth-grade students. Data were collected through triangulation techniques, namely passive participant observation during the learning process, semi-structured interviews with class teachers, and in-depth document analysis of students' pre-test and post-test descriptive essay scripts. Data analysis was conducted interactively through reduction, presentation, and conclusion drawing, and using an analytical rubric developed to measure accuracy in these three linguistic aspects. The results revealed different impacts of flashcards on each aspect. On the one hand, this media proved very effective in improving the quality of students' diction. The visual images on flashcards acted as a significant cognitive scaffold in enriching vocabulary, increasing lexicon variety, and encouraging the use of more concrete, sensory, and contextual words. On the other hand, the study found that improvements in spelling and punctuation were very limited. Errors such as incorrect capitalization, errors in prepositions (*di-*), inconsistent spelling of standard words, and the absence or misplacement of periods and commas were still very common. These findings indicate that while flashcards are effective as idea generators and diction enhancers, they do not automatically improve mastery of written language conventions, which are often arbitrary and mechanical.